Handbook of infant mental health - Zeanah, Charles H. (Guilford, 1993)
I. The context of infant mental health * Models of development and developmental risk / Arnold J. Sameroff * The family context of infant mental health: I. Affective development in the primary caregiving relationship / Karlen Lyons-Ruth and Charles H. Zeanah, Jr. * The family context of infant mental health: II. Infant development in multiple family relationships / Susan Crockenberg, Karlen Lyons-Ruth and Susan Dickstein * The sociocultural context of infant development / Cynthia T. Garcia Coll and Elaine C. Meyer II. Risk conditions and protective factors * Poverty and infant development / Robert Halpern * Prematurity and serious medical illness in infancy: Implications for development and intervention / Klaus Minde * Adolescent parenthood: Risks and opportunities for mothers and infants / Joy D. Osofsky, Della M. Hann and Claire Peebles * Parental mental illness and infant development / Ronald Seifer and Susan Dickstein * Maternal substance abuse and infant development / Barry Zuckerman and Elizabeth R. Brown * Maltreatment and infant development / Patricia J. Mrazek III. Assessment * Clinical interviews with infants and their families / Laurence M. Hirshberg * Assessment of developmental status and parent-infant relationships: The therapeutic process of evaluation / Roseanne Clark, Andrew Paulson and Susan Conlin * Use of structured research procedures in clinical assessments of infants / Judith A. Crowell and Melissa A. Fleischmann IV. Disorders of infancy * Classification and the diagnostic process in infancy / Robert N. Emde, Richard D. Bingham and Robert J. Harmon * Autism and the pervasive developmental disorders / Fred R. Volkmar * Mental retardation / Michael Thomasgard and Jack P. Shonkoff * Communication disorders in infants and toddlers / Barry M. Prizant, Amy M. Wetherby and Joanne E. Roberts * Regulatory disorders / Stanley I. Greenspan and Serena Wieder * Post-traumatic stress disorder / Martin J. Drell, Clifford H. Siegel and Theodore J. Gaensbauer * Sleep disorders / Avi Sadeh and Thomas F. Anders * Failure to thrive and feeding disorders / Diane Benoit * Disorders of attachment / Charles H. Zeanah, Jr., Oommen K. Mammen and Alicia F. Lieberman * Psychosomatic processes and physical illnesses / David A. Mrazek V. Intervention * A multidimensional analysis of early childhood intervention programs / Samuel J. Meisels, Margo Dichtelmiller and Fong-ruey Liaw * Preventive interventions: Enhancing parent-infant relationships / Kathryn E. Barnard, Colleen E. Morisset and Susan Spieker * Family support programs / Bernice Weissbourd * Interaction guidance: Understanding and treating early infant-caregiver relationship disturbances / Susan C. McDonough * Infant-parent psychotherapy / Alicia F. Lieberman and Jeree H. Pawl VI. Social applications of infant mental health * Infant day care / Marianne Barton and Martha Williams * Infant placement and custody / Thomas M. Horner and Melvin J. Guyer * Infant mental health and social policy / Edward Zigler, Pauline Hopper and Nancy W. Hall